PENAHANAN DAN EKSEKUSI PEMIDANAAN ANAK YANG TIDAK DITEMPATKAN DI LPAS DAN LPKA - Mega Mustika Noviyanti; Setiyono (Fakultas Hukum Universitas Trisakti, 2023)
Children are the generation that will shape the course of the country. For them to develop into mentally and physically fit youngsters as well as future seeds, children need guidance and preparation from an early age. Juvenile delinquency always rises year, thus measures to stop it must be supported and regulated by law. It is said that a youngster committed stealing in case number 6/Pid.Sus-Anak/2022/PNSrg. The formulation of the problem in this thesis is how to carry out the detention of children during the investigation and trial, as well as how to carry out the punishment of children in the case. Normative legal research is the method of inquiry used in this thesis. The research's analytical descriptive nature calls for a qualitative approach to data processing. The findings of the research and discussion demonstrate that the detention of the suspect while he was still a minor during the investigation phase of the case up until his sentencing did not follow the guidelines outlined in Article 1 Point 21 of the SPPA Law because the suspect was held at the Serang Police Detention Center throughout the investigation phase and trial phase of the case. The manner in which the punishment was carried out following the judgement did not adhere to the rules outlined in Article 1 Number 20 of the SPPA Law because the implementation of the sentence against the convict is carried out at the Serang Police Detention Center.